![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
+)\(\sqrt{x+2\sqrt{x-1}}+\sqrt{x-2\sqrt{x-1}}\)= 2
\(\sqrt{x-1+2\sqrt{x-1}+1}+\sqrt{x-1-2\sqrt{x-1}+1}=2\)
\(\sqrt{\left(x-1+1\right)^2}+\sqrt{\left(x-1-1\right)^2}=2\)
\(\sqrt{x^2}+\sqrt{\left(x-2\right)^2}=2\)
\(x+x-2=2\)
\(2x=4\)
\(x=2\)
+) Hình như sai đâu bài chỗ \(\sqrt{x+3+4\sqrt{x+1}}\)
\(\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(Q=\left(\frac{\sqrt{x}^2-1}{2\sqrt{x}}\right)^2.\left[\frac{\left(\sqrt{x}-1\right)^2-\left(\sqrt{x}+1\right)}{\left(\sqrt{x}+1\right)\left(\sqrt{x}-1\right)}\right]\)
\(Q=\left[\frac{\left(\sqrt{x}+1\right)\left(\sqrt{x}-1\right)}{2\sqrt{x}}\right].\left[\frac{\left(\sqrt{x}-1+\sqrt{x}+1\right)\left(\sqrt{x}-1-\sqrt{x}-1\right)}{\left(\sqrt{x}+1\right)\left(\sqrt{x}-1\right)}\right]\)
\(Q=\frac{\left(\sqrt{x}+1\right)\left(\sqrt{x}-1\right)}{2\sqrt{x}}.\frac{-4\sqrt{x}}{\left(\sqrt{x}+1\right)\left(\sqrt{x}-1\right)}\)
\(Q=\frac{-4\sqrt{x}}{2\sqrt{x}}=-2\)